The structured interview of family assessment risk: convergent validity, inter-rater reliability and structural relations - Santos, D. J. F.; Alberto, I. M. M.; Marques, C. M. V. A. (Child and Adolescent Social Work Journal, 2016)
The quality of parenting, composition and socio-economic status are family risk or protective factors on juvenile delinquency, however, there is not an instrument to help psychologists and social workers to specifically assess the adolescent offender’s family. This study set out to accomplish an additional validation study of the structured interview of family assessment risk (SIFAR), a structured professional judgment tool for the assessment of family risk and protective factors of juvenile delinquents. The statistical analyses included inter-rater reliability, convergent validity with YLS/CMI, the Partial Least Squares approach to structural equation modeling and receiving operator characteristics (ROC) analysis. A sample of 130 male adolescent delinquents detained in Portuguese forensic facilities and their parents, were paired analyzed. The YLS/CMI was used to analyze the convergent validity with SIFAR. SIFAR shows a strong correlation with the YLS/CMI family context, moderate to high values of inter-rater reliability; SIFAR factors show that they are predictive determinants of the Moderate Four risk factors. ROC analysis shows adequate accuracy power. The findings show that SIFAR it is useful as an additional assessment tool for structured risk assessment instruments since it allows understanding the vulnerabilities and strengths of the delinquent’s family.